If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 * 4x + -24 = 8 + 2x + 2x + -4 Multiply 2 * 4 8x + -24 = 8 + 2x + 2x + -4 Reorder the terms: -24 + 8x = 8 + 2x + 2x + -4 Reorder the terms: -24 + 8x = 8 + -4 + 2x + 2x Combine like terms: 8 + -4 = 4 -24 + 8x = 4 + 2x + 2x Combine like terms: 2x + 2x = 4x -24 + 8x = 4 + 4x Solving -24 + 8x = 4 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -24 + 8x + -4x = 4 + 4x + -4x Combine like terms: 8x + -4x = 4x -24 + 4x = 4 + 4x + -4x Combine like terms: 4x + -4x = 0 -24 + 4x = 4 + 0 -24 + 4x = 4 Add '24' to each side of the equation. -24 + 24 + 4x = 4 + 24 Combine like terms: -24 + 24 = 0 0 + 4x = 4 + 24 4x = 4 + 24 Combine like terms: 4 + 24 = 28 4x = 28 Divide each side by '4'. x = 7 Simplifying x = 7
| 5(w-3)=7w-27 | | 32=2w+2+2w | | 3x^7+24x^6+43x^5+92x^4+134x^3-20x^2+40x-16=0 | | 1949=917+6(123+h-22) | | -9c+18s= | | 2*4x=8+2x+2x-4-24 | | 36=(x+2)x | | 50+4y-15=14y-14-3y | | 2(-2)-4= | | -5(2x+4)+5x=10 | | 2/3(6x+12)=16 | | 3(2n+1)=8(6n+2)+1 | | 2x^2+8x=x^2+33 | | 4x+5(x+1)=4(x-3) | | 8x-3x-93=8x+48 | | (3m-2n)(3m+2n)= | | 10x-2(x-2)=8(x+1)+3 | | X+7x=-4x | | -5x-37=-12 | | 5x-25y=10 | | 144r^2+169= | | Y=.5 | | -1d-2=42 | | 0.4x+1.6=0.9x-1.4 | | 2t^2-4.2t+459=869 | | 0=8x^2+134x-189 | | .25+8x=.50+6x | | X+x+5=152 | | 7(6+x)=6(x-6) | | 3xX+6=45 | | 9-4x=9x+10 | | 16x=8x |